2012
DOI: 10.1177/1550059411429531
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and the Efficacy of qEEG-Guided Neurofeedback Treatment

Abstract: Schizophrenia is sometimes considered one of the most devastating of mental illnesses because its onset is early in a patient's life and its symptoms can be destructive to the patient, the family, and friends. Schizophrenia affects 1 in 100 people at some point during their lives, and while there is no cure, it is treatable with antipsychotic medications. According to the Clinical Antipsychotic Trials for Interventions Effectiveness (CATIE), about 74% of the patients who have discontinued the first medication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 90 publications
1
41
0
Order By: Relevance
“…An increasing number of studies have demonstrated that neurofeedback is a potential and non-pharmacological supportive treatment for many neurological and psychiatric disorders which are accompanied by abnormal patterns of cortical activity such as attention deficit hyperactivity disorder (ADHD; Arns et al, 2009; Duric et al, 2012; Moriyama et al, 2012), depression (Choi et al, 2011; Dias and van Deusen, 2011), substance abuse (Sokhadze et al, 2008), and schizophrenia (Bolea, 2010; Nan et al, 2012a; Surmeli et al, 2012). In addition to clinical applications, neurofeedback has also shown the potential for skills enhancement in healthy individuals (Vernon, 2005; Gruzelier et al, 2006; Gruzelier, 2013a), e.g., cognitive abilities (Vernon et al, 2003; Hanslmayr et al, 2005; Zoefel et al, 2011), memory (Nan et al, 2012b; Wang and Hsieh, 2013), peripheral visual performance (Nan et al, 2013), creativity and artistic performance (Egner and Gruzelier, 2003; Gruzelier, 2009, 2013b; Gruzelier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated that neurofeedback is a potential and non-pharmacological supportive treatment for many neurological and psychiatric disorders which are accompanied by abnormal patterns of cortical activity such as attention deficit hyperactivity disorder (ADHD; Arns et al, 2009; Duric et al, 2012; Moriyama et al, 2012), depression (Choi et al, 2011; Dias and van Deusen, 2011), substance abuse (Sokhadze et al, 2008), and schizophrenia (Bolea, 2010; Nan et al, 2012a; Surmeli et al, 2012). In addition to clinical applications, neurofeedback has also shown the potential for skills enhancement in healthy individuals (Vernon, 2005; Gruzelier et al, 2006; Gruzelier, 2013a), e.g., cognitive abilities (Vernon et al, 2003; Hanslmayr et al, 2005; Zoefel et al, 2011), memory (Nan et al, 2012b; Wang and Hsieh, 2013), peripheral visual performance (Nan et al, 2013), creativity and artistic performance (Egner and Gruzelier, 2003; Gruzelier, 2009, 2013b; Gruzelier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This, then, results in different electrophysiological presentations being treated differently, even if the overarching diagnosis is the same. This clinical approach is supported through multiple reports in the literature discussing how training the deviant zscores towards the mean (i.e., normalize the qEEG) in qNF results in the greatest clinical benefit (Arns et al, 2012;Breteler, Arns, Peters, Giepmans, & Verhoeven, 2010;Collura, 2008;Sürmeli et al, 2012;Sürmeli & Ertem, 2009Walker, 2009Walker, , 2010Walker, , 2011Walker, , 2012a.…”
Section: Normalization Model Of Qnfmentioning
confidence: 65%
“…In understanding that a particular clinical symptom presentation may be related to varied deviations in the qEEG, it quickly becomes apparent that each NF protocol needs to be personalized to the client; as well as monitored and modified for maximum treatment effect (Sürmeli, Ertem, Eralp, & Kos, 2012). This, then, results in different electrophysiological presentations being treated differently, even if the overarching diagnosis is the same.…”
Section: Normalization Model Of Qnfmentioning
confidence: 99%
See 1 more Smart Citation
“…The EEG-NFB has been tested as a treatment in a vast domain of neurological and psychiatric disorders, e.g., epilepsy (Sterman and Friar, 1972; Kotchoubey et al, 2001), attention deficit hyperactivity disorder (ADHD; Kaiser and Othmer, 2000; Fuchs et al, 2003; Kropotov et al, 2007), schizophrenia (Gruzelier et al, 1999; Surmeli et al, 2012) and even in traumatic brain injury (TBI) and stroke rehabilitation (for the review of clinical applications, see Yucha and Montgomery, 2008). In healthy subjects the EEG-NFB has been applied expecting behavioral and/or cognitive improvements (Arns et al, 2008; Reiner et al, 2014) and as a supportive training of cognitive performance in the elderly (Becerra et al, 2012; Staufenbiel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%